Evolution and development of female religious schools in Spain - Maria Fernanda Piñero Sampayo (Revista Brasileira de História da Educação, 2015)
In Spain the education, which can be defined as private, was traditionally held by the Church, which carried out the task of educating through their educational institutions. The causes of this predominance mainly reflect the Catholic tradition of the country, but in addition, from the nineteenth century on, when an increasing number of citizens accesses studies, the schools of the Church learned how to respond to a growing demand that state institutions seemed unable to satisfy. These circumstances, together with other causes, led the schools run by these organizations spread over the Spanish territory in urban situations, and consolidate as the preferred option for a rising social sector, the middle class, who chose to train especially for his daughters, religious schools.